Pharmacotherapy virtual attachment during COVID-19 pandemic: use of online experiential assessment in a Malaysian pharmacy school - Elnaem, Mohamed Hassan Abdelaziz; Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz (International Pharmaceutical Federation (FIP), 2020)
This case study aims to report the efforts made by International Islamic University Malaysia to pursue the experiential pharmacotherapy attachment for the final-year of pharmacy students via online mediums in the light of the COVID-19 restrictions on face-to-face clinical experiential learning. A four-week virtual pharmacotherapy experiential attachments were redesigned and conducted via an online platform (Google Meet). Students were required to have a two-hour virtual discussion and consultation session with their preceptors twice a week throughout the attachment period. In each week, students were provided with real-life clinical cases that were chosen by their preceptors from the Department of Pharmacy Practice’s clinical case repository. Students were assessed via clinical case reports, virtual seminar presentations, weekly virtual discussions with preceptors, and virtual objective structured clinical examinations. All the virtual sessions were conducted on a synchronous basis to assure students’ active participation. Alongside this, a revised online final assessment was also designed.